1999
DOI: 10.1530/jrf.0.1150293
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen-dependent expression of LH/hCG receptors in pig Fallopian tube and their role in relaxation of the oviduct

Abstract: The current studies investigated the concentration and distribution of LH receptors in the oviduct of ovariectomized gilts at various times after administration of oestradiol benzoate (10 \g=m\gkg\m=-\1body weight) to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 24 publications
(33 reference statements)
0
59
0
5
Order By: Relevance
“…Helguera et al (2009) and Girotti and Zingg (2003) reported AQP5 and AQP8 expression in rat myometrium by microarray or quantitative RT-PCR (qRT-PCR) and by microarray, respectively. Immunohistochemical experiments performed by Gawronska et al (1999Gawronska et al ( , 2000 revealed luteinizing hormone/human chorionic gonadotropin (LH/hCG) receptor protein expression in the epithelium of tubal mucosa, smooth muscle cells, and blood vessel endothelium in pigs. However, LH/hCG receptors in the mouse were detected in the serosa and subepithelial cells but not in the epithelium of the oviduct (Zhang et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Helguera et al (2009) and Girotti and Zingg (2003) reported AQP5 and AQP8 expression in rat myometrium by microarray or quantitative RT-PCR (qRT-PCR) and by microarray, respectively. Immunohistochemical experiments performed by Gawronska et al (1999Gawronska et al ( , 2000 revealed luteinizing hormone/human chorionic gonadotropin (LH/hCG) receptor protein expression in the epithelium of tubal mucosa, smooth muscle cells, and blood vessel endothelium in pigs. However, LH/hCG receptors in the mouse were detected in the serosa and subepithelial cells but not in the epithelium of the oviduct (Zhang et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for LH have been identified in many extragonadal sites (Rao 2001), furthermore there is a compelling relationship between LH receptor expression and the sensitivity of the same site to oestrogen (Gawronska et al 1999) and expression of LH receptors has been linked to changes in oestrogen status in several species (Gawronska et al 1999;Akazome and Mori 1999;Knecht et al, 1984). Since bone-forming osteoblasts have been found to express receptors for estrogen (Komm et al 1988, Eriksen et al 1988) it was also a possibility that these same cells might also express receptors for LH.…”
Section: Discussionmentioning
confidence: 99%
“…Skin, mammary gland, uterus and urinary bladder express LH receptors and respond to changes in estrogen status. Of additional significance is the fact that estrogen can influence LH receptor expression and therefore the sensitivity of target tissues to this gonadotropin as observed, for example, in the epithelial tissue of the pig oviduct (Gawronska et al, 1999). Collectively, these findings imply that LH elicits a diverse array of cell and tissue responses other than ensuring the regulation of gonadal function.…”
Section: Introductionmentioning
confidence: 98%
“…by GnRH agonist or antagonist pretreatment, or by increasing the number of LHRs in the tumor e.g. by pre-treatment with estradiol (Gawronska et al 1999), could enhance the treatment outcome in granulosa cell tumors.…”
Section: In Vivo Trials Of Hecate-cgβ Conjugatementioning
confidence: 99%